From local flavor to global fandom: an exploration of the cultural presentation and attitudes towards using English by Thai content creators on the TikTok platform - Huttayavilaiphan, Rutthaphak (Frontiers in Communication, 2024)
This study explores the cultural presentation and attitudes towards using English among Thai TikTokers, focusing on how they create and present cultural content. Utilizing detailed content analysis of video titles, descriptions, and comments, alongside semi-structured interviews with 20 selected TikTokers, the research reveals the diverse motivations and challenges faced by these creators. The findings highlight a wide range of cultural content, including ethnic, lifestyle, national, subcultures, and youth cultures, which serve to engage audiences and promote cultural exchange. The study also identifies the overlapping nature of cultural presentation strategies, such as visual storytelling, educational content, user engagement, and the strategic use of hashtags and multilingual content. These strategies are designed to increase the visibility and impact of their content, enhancing a sense of global community and cultural understanding. The study categorizes attitudes towards using English into positive, negative, and mixed. While some TikTokers embrace English to broaden their international reach and facilitate intercultural communication, others express concerns about language proficiency, such as accents and grammatical accuracy, which may lead to negative feedback. This complexity underscores the challenges of multilingual content creation, balancing cultural authenticity with global engagement. By linking these findings with existing theories and studies, the research offers a comprehensive understanding of digital cultural representation on social media platforms. The insights contribute to the broader field of social media studies, providing implications for future research on content strategies, cultural communication, and the role of language in digital media.